Influence of Double Parameter Modification on Transmutation Point Location of Planar Double- enveloping Worm Pair - Zhang Yuemin; Yin Xinbin; Wang Yuqing (Jixie chuandong)
The transmutation point location is achieved according to the enveloping worm pair mesh equation. The tooth parameter equations of enveloping worm pair transmutation point is established and the relationship between transmutation point and worm gear tooth surface when the transmission ratio and center distance changing separately and at the same time are respectively discussed. Then,the fitting curves of the transmutation point changing with the transmission ratio and center distance,the relationship of them is illustrated. The conclusion that the transmutation point is more and more far away from the worm gear tooth surface with the increasing of the transmission ratio and center distance is obtained. It has important practical significance of the processing and the structural analysis of worm gear tooth surface,worm pair manufacturing,assembly and parameter modification.